MOOC-Based PBL Model to Improve Chemical Literacy Skills In Content, Procedural and Epistemic Knowledge Aspects - Mahbub Alwathoni; Sulistyo Saputro; Sri Yamtinah; Mohammad Masykuri; Suwahono Suwahono (International Journal of Pedagogy and Teacher Education, 2024)
This study explores the effectiveness of a MOOC-based Problem-Based Learning (PBL) model in enhancing chemical literacy across three dimensions—content, procedural, and epistemic knowledge—among grade 10 high school students. Employing an explanatory sequential mixed-methods design, the research gathered data through chemical literacy tests, interviews, and observations. The participants comprised 80 students from three districts in Central Java, Indonesia. Quantitative analysis using Rasch modeling revealed a significant improvement in scores, with an average pretest score of 44.82, increasing to 66.50 post-intervention. The effect size of 1.1819 was categorized as "good," indicating the model's potential for fostering learning. However, the average post-test score remained below the minimum completion criterion of75.80. Qualitative findings highlighted weaknesses in the problem orientation stage of the PBL model, particularly in connecting students’ prior knowledge to new learning objectives. This stage is critical for setting the foundation for subsequent PBL phases, suggesting that insufficient scaffolding may have hindered optimal learning outcomes. To enhance the effectiveness of MOOC-based PBL, the study recommends restructuring the problem orientation stage to align better with students' initial knowledge levels. These findings underscore the promise of integrating MOOC-based PBL in chemistry education while emphasizing the need for refinements to address identified challenges. By bridging gaps in problem orientation and fostering deeper connections between prior and new knowledge, this approach could more effectively support the development of chemical literacy, providing valuable insights for educators and policymakers.